Lives and spaces: photovoice and offender supervision in Ireland and England - Fitzgibbon, Wendy (Criminology & criminal justice, 2019)
The lives and experiences of those on probation supervision are often invisible and dismissed as unimportant or worse as ‘an easy option’. This article reviews two different studies in England and Ireland which utilized an innovative technique, Photovoice, to foreground the experiences of probationers on their journey towards desistance. The difficulties they face such as stigma, social judgement and exclusion are explored as well as their need for emotional calm, and support and understanding from their supervisors and the wider community. Photovoice as a methodological and creative tool is revealed as a novel and expressive means to develop insight into probation supervision and an effective technique for undertaking cross-national research which can communicate across cultural boundaries.